Vocabulary of the modern Russian language from the point of view of stylistic diversity - Dawood, Sarah Salman; Abbas, Yaseen Hamza (Al-Adab Journal, 2022)
This Russian article is devoted to identifying and describing functional patterns in the Russian language. The work will present a stylistic characteristic of borrowed vocabulary, which in some cases replaces the original Russian words, which can also lead to a lack of understanding of the meaning of speech, its euphemism, in addition, it can fill some specific stylistic cliches formed by structural changes in the system of styles of the Russian language.Loanwords can contain features of literary and colloquial language.